Analisis Rasio Likuiditas dan Solvabilitas untuk Mengukur Kinerja Keuangan PT Jaya Trishindo Tbk - Salsabila, Zakiya (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the financial performance of PT. Jaya Trishindo Tbk. using liquidity and solvency ratios during the period 2019–2023. The approach used is a descriptive qualitative method, with secondary data obtained through literature reviews and the company's annual financial reports. Liquidity ratios include the current ratio and cash ratio, while solvency is analyzed through the debt to asset ratio (DAR), debt to equity ratio (DER) and non-current liability to equity. The results of the study show that the company experienced a decrease in liquidity and an increase in financial risk during 2019–2023. The Current Ratio and Cash Ratio indicate an inability to meet short-term obligations, especially in 2022–2023. Dependence on debt has increased significantly, as seen from the high Debt to Asset Ratio and Debt to Equity Ratio. The Non-Current Liability to Equity Ratio shows large fluctuations, with a significant increase until 2022 and a drastic decrease in 2023, reflecting efforts to reduce the long-term debt burden. Companies need to take real steps to improve liquidity and funding structure in order to maintain operational stability and sustainability in the future.